FESTIVAL KEBUDAYAAN CANBERRA SEBAGAI ALAT DIPLOMASI PEMERINTAH INDONESIA DI AUSTRALIA (2014-2015) - Halifa Haqqi, Setyasih Harini & (Transformasi, 2017)
Culture is regarded as forming international bridges and interactions. With culture, state canreach influential members of foreign societies who cannot be reached through traditionalembassy function. Bilateral cooperation between Indonesia and Australia is like a roller coasteror love-hate relationship. This study purpose to explain Canberra Festival as tool of culturaldiplomacy of Indonesia in Australia. It is qualitative research with literature as source of data.The object is art performance of Indonesia dancer through Canberra Festival in Australia.Indonesia has more opportunities make cultura performance through Canberra Festival afterhacking incident. Result of the research show culture diplomacy through Canberra Festival canimprove relationship between Indonesia-Australia after hacking accident. The conclusion isCanberra Festival can increase tourist from Australia.Key words: foreign relationship, national interest, cultural diplomacy